Investigation of chip formation mechanism in ultra-precision diamond turning of silk fibroin film. (February 2022) - Wang, Zhengjian; Luo, Xichun; Sun, Jining; Seib, Philipp; Phuagkhaopong, Suttinee; Chang, Wenlong; Gao, Jian; Mir, Amir; Cox, Andrew
Abstract: The importance of silk fibroin particles (size from tens of nanometres to hundreds of microns) as effective drug carriers has been well identified due to their superior mechanical strength, biocompatibility and biodegradability. They are usually fabricated by methods that have difficulties in controlling the size and shape to meet the required functions. In addition, using chemical agents in the fabrication process may result in biological risks and degradation of the fibroin structures. In this study, ultra-precision diamond turning (UPDT) technology is researched as an alternative chemical-free manufacturing approach to generate silk particles in the form of cutting chips with controllable size and shape. The machinability in UPDT of silk fibroin film (hereinafter referred to as silk film) was discussed in terms of specific cutting force and chip morphology. The material removal in UPDT of silk film is taken place in the ductile regime. Experimental results reveal that a rise in the cutting speed could significantly reduce the specific cutting force, while decreasing the depth of cut (DOC) could increase the specific cutting force because of the size effect. Moreover, a sharp point tool using a less than 2.5 μm/rev feed rate is preferred to generate helical silk chips. The formation mechanism of shear bands and serrated chips in UPDT of silk film was investigated with the aid of a finite element and smoothed particle hydrodynamics (FE-SPH) hybrid numerical model with Cowper-Symonds (CS) material equation. The material parameters of silk film were determined for the first time at p = 7 and D = 1140 s −1 . The simulated specific cutting force with this set of material parameters is 49.0% smaller than the measured one. The simulated chip morphology (e.g. shear band spacing) was also in good agreement with the measured values. The simulation study shows that the shear band formation is done via two joining parts: one part propagates from the cutting edge to the free surface, another part initiates on the free surface and evolves towards the cutting edge. The chip segment is formed by a microcrack propagating from the free surface to the cutting edge. The underlying mechanism of formation of the serrated chip is found to have its roots in the hierarchical structure of silk fibroin. Graphical abstract: Unlabelled Image Highlights: The machinability in ultra-precision diamond turning of silk film was studied, while the ductile mode cutting was achieved. The chip formation mechanism was revealed with the aid of the established FE-SPH hybrid numerical model. The shear band is formed via two parts: one evolves from the cutting edge to the free surface, another one goes oppositely. The underlying serrated chip formation mechanism is found to have its roots in the hierarchical structure of silk fibroin.